LEGAL REVIEW CONTRACT WORKERS RIGHTS (OUTSOURCING) IN ACHIEVING SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Suhartono, Tonny; Setiyono, Joko (Tadulako University, 2021)
Labor problems will be very complex in line with the era of globalization and the rapid development of all fields, especially in the industrial sector, especially considering the high number of workers in Indonesia today. Another factor that is the source of labor problems is the unfulfilled interests of workers' rights. Therefore, efforts are needed to improve the rights of contract workers and promote a healthy and safe work environment. This study aims to examine the rights of contract workers based on existing laws in Indonesia. Also, this research will examine the contextualization of the Sustainable Development Goals (SDGs) as an effort to improve the rights of contract workers. This research uses normative legal research. The approach used is a statutory approach and a conceptual approach. The data used are secondary data which were analyzed using descriptive-qualitative analysis techniques. The results of this study indicate that the development approach in the economic sector in sustainable development focuses on increasing workers' skills so that they can increase competitiveness in obtaining decent work. This of course can be achieved by fulfilling workers' rights. Indonesia needs to demonstrate its commitment to the implementation of the SDGs, particularly Goal 8 on decent work and economic growth. Indonesia is one of the countries that approved the formation of SDGs, therefore the responsibility for achieving the SDGs is also the responsibility of Indonesia, from the central government to regional governments.